Enhancing the Visibility of Handicraft-Based MSMEs through Strategic Web Design - Nisa, Atifa Raidatun; Zulaikha, Ellya (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to develop a strategic web design approach for micro or small enterprises focusing on workshop-based creative industries, using FGH (an enterprise specializing in handcrafted shibori techniques) as a case study. The research adopts a design thinking approach, encompassing five stages: empathize, define, ideate, prototype, and test. Data were collected through interviews and observations involving the business owner and potential customers. Two key personas emerged: “The Curious Creative” and “The Craft Entrepreneur,” with the design focus on the latter. During the define stage, user needs were synthesized using the empathy map, Customer Journey Map (CJM), and Value Proposition Canvas (VPC). The ideate phase involved collaborative brainstorming sessions guided by the five dimensions of experiential marketing: sense, feel, think, act, and relate. Ideas were then validated with stakeholders for relevance and feasibility. The findings reveal a demand for a digital platform that not only provides workshop information but also supports learning processes, community engagement, and access to an alumni marketplace. This research contributes to understanding user-centered digital strategies for creative micro-enterprises, particularly those offering experiential-based services.